Novosti v evropskem družinskem pravu - nova ureditev v preživninskih zadevah - Novak, Barbara (Pravni letopis, 2011)
The Maintenance Regulation deals with provisions on jurisdiction, recognition and enforcement of foreign judicial decisions, legal aid and administrative cooperation. The main goal of the regulation is to protect the maintenance creditor as the weaker party. The near analysis of the new maintenance regulation reflects some important trends going on in the entire inter national private law: the connecting factors such as nationality and permanent residence have lost their importance, instead of them the habitual residence is now gaining on relevance; the possibility of choosing the law is widely encouraged by European law, even in the field of a family (maintenance) law where the party autonomy was recently still widely restricted.
Keywords: družinsko pravo; European family law; European Union; Evropska unija; evropsko družinsko pravo; Haaške konvencije; Haaški protokol; Maintenance Regulation; preživnine; preživninske odločbe; recognitions and enforcement of maintenance decisions; sodne odločbe; The Hague Convention and Protocol; uredba v zadevah preživljanja